What IAPT CBT High-Intensity Trainees Do After Training. Issue 1 (28th July 2016) - Liness, Sheena; Lea, Susan; Nestler, Steffen; Parker, Hannah; Clark, David M.
Abstract : Background: The UK Department of Health Improving Access to Psychological Therapies (IAPT) initiative set out to train a large number of therapists in cognitive behaviour therapies (CBT) for depression and anxiety disorders. Little is currently known about the retention of IAPT CBT trainees, or the use of CBT skills acquired on the course in the workplace after training has finished.Aims: This study set out to conduct a follow-up survey of past CBT trainees on the IAPT High Intensity CBT Course at the Institute of Psychiatry, Psychology and Neuroscience (IoPPN), King's College London (KCL), one of the largest IAPT High Intensity courses in the UK.Method: Past trainees ( n = 212) across 6 cohorts (2008-2014 intakes) were contacted and invited to participate in a follow-up survey. A response rate of 92.5% ( n = 196) was achieved.Results: The vast majority of IAPT trainees continue to work in IAPT services posttraining (79%) and to practise CBT as their main therapy modality (94%); 61% have become CBT supervisors. A minority (23%) have progressed to other senior roles in the services. Shortcomings are reported in the use of out-of-office CBT interventions, the use of disorder-specific outcome measures and therapy recordings to inform therapy and supervision.Conclusions: Past trainees stay working in IAPT services and continue to use CBT methods taught on the course. Some NICE recommended treatment procedures that are likely to facilitate patients' recovery are not being routinely implemented across IAPT services. The results have implications for the continued roll out of the IAPT programme, and other future large scale training initiatives.